2013
DOI: 10.1021/bi4004952
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of O6-Pyridyloxobutyl-2′-deoxyguanosine Repair by Human O6-alkylguanine DNA Alkyltransferase

Abstract: Tobacco-specific nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N-nitrosonicotine (NNN) are potent carcinogens believed to contribute to the development of lung tumors in smokers. NNK and NNN are metabolized to DNA-reactive species that form a range of nucleobase adducts, including bulky O6-[4-oxo-4-(3-pyridyl)but-1-yl]deoxyguanosine (O6-POB-dG) lesions. If not repaired, O6-POB-dG adducts induce large numbers of G → A and G → T mutations. Previous studies have shown that O6-POB-dG can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…The hyperbolic fit to the 1/τ 1 values shown in Figure 3 must be considered to be approximate because the experimental conditions limited the range of AGT concentrations that could be employed while maintaining pseudo‐first order conditions. However, a K d for AGT binding of 560 ± 40 nM (5 °C) is in reasonable agreement with the value reported previously (1.5 μM, 22 °C), [ 39 ] which was determined using a different technique (gel shift assay) that includes the energetic contributions from all steps in the binding and flipping processes. The forward rate constant for the second step of k 2 = 530 ± 40 seconds −1 at 5 °C (equivalent to a second order constant of ~3 x 10 8 M −1 second −1 for an AGT concentration of 1.6 μM) is more than two orders of magnitude greater than the repair rate constant for AGT with this modified DNA (1.79 x 10 6 M −1 second −1 ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The hyperbolic fit to the 1/τ 1 values shown in Figure 3 must be considered to be approximate because the experimental conditions limited the range of AGT concentrations that could be employed while maintaining pseudo‐first order conditions. However, a K d for AGT binding of 560 ± 40 nM (5 °C) is in reasonable agreement with the value reported previously (1.5 μM, 22 °C), [ 39 ] which was determined using a different technique (gel shift assay) that includes the energetic contributions from all steps in the binding and flipping processes. The forward rate constant for the second step of k 2 = 530 ± 40 seconds −1 at 5 °C (equivalent to a second order constant of ~3 x 10 8 M −1 second −1 for an AGT concentration of 1.6 μM) is more than two orders of magnitude greater than the repair rate constant for AGT with this modified DNA (1.79 x 10 6 M −1 second −1 ).…”
Section: Resultssupporting
confidence: 91%
“…The forward rate constant for the second step of k 2 = 530 ± 40 seconds −1 at 5 °C (equivalent to a second order constant of ~3 x 10 8 M −1 second −1 for an AGT concentration of 1.6 μM) is more than two orders of magnitude greater than the repair rate constant for AGT with this modified DNA (1.79 x 10 6 M −1 second −1 ). [ 39,40 ] The rate constants for binding ( k 1 ) and release ( k −1 ) of AGT must exceed this value in order to yield the observed hyperbolic dependence. These rate constants presumably report on both AGT binding and one‐dimensional sliding on the DNA to find the alkylated base.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high mutation frequency observed for the lesion suggests that it is not efficiently repaired prior to being encountered by the DNA replication machinery. Along this line, several recent studies have shown that O 6 -POB-dG can be directly repaired by O 6 -alkylguanine-DNA alkyltransferase (AGT) (33,34). Following the transfer of a methyl or other alkyl groups from O 6 -alkylguanine to an internal cysteine residue (Cys-145) of AGT, O 6 -dG adducts are repaired, and the protein becomes inactivated during the repair process (35,36).…”
Section: Translesion Synthesis Of O-alkylated Dna Adductsmentioning
confidence: 99%